Analysis of the determinants of Atlético and Cruzeiro fans' loyalty to the thematic shops (Revista de Administração, 2013)
This study aimed to identify and analyze the variables that influence the loyalty process of Atlético Mineiro and Cruzeiro's fans in Belo Horizonte, Brazil, in relation to the consumption of the official products of these teams. Structured on a theoretical model to identify loyalty attributes, this research was developed with 300 customers, whose data were subjected to univariate and multivariate analysis. The results, obtained by means of structural equation modeling, confirm that products and services supply positively impacts the investment, the dependence feeling and the reliance. It was found that the greater the investment in the business relationship, the greater the client's dependence feeling; the more intense the exchange of information, the greater the confidence feeling; the greater the dependence and the reliance, the greater the customer's commitment to the business relationship; and the greater the commitment, the greater the loyalty to the company. The proposed model explained 53.6% of the interrelationships between the constructs and the relationship of these with its manifest variables. The measurement model explained 53.1% of the constructs variability and the structural model explained 54.1% of these same variables. Since this is a social research, in which the control of the responses is more limited, these results were considered satisfactory, because they can explain more than half of the variability of the assessed variables.